ENHANCED BIOHYDROGEN PRODUCTION THROUGH REPEATED-BATCH FERMENTATION OF RICE-BRAN - EBENEZER O. DADA; ABASS O. ALADE; ADEMOLA T. ADENIJI; TINUADE J. AFOLABI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Repeated-batch fermentation experiments were carried out to determine the best switching time, stability, and consistency of the process for enhanced biohydrogen production from Rice-bran. After the initial batch process, one repeated Cycle was made for three ‘runs’ to determine the best switching time, the ‘runs’ were terminated after 45 h, 60 h and 75 h, respectively. The effect of switching time on cell growth, hydrogen yield and productivity was investigated. The pattern of cell growth suggested that switching from batch mode to repeated batch mode at the 60th h led to the production of the highest amount of hydrogen. The lowest pH value (5.22) was observed at the end of the first fermentation Cycle. Cycle 2 has the highest amount of cumulative hydrogen production (mL 1280.3 L-1 medium) and the highest pH value (5.38). The profiles of the biomass concentration for all the Cycles were similar showing the stability and consistency of the process. There was an increment of 22 % in the overall Hydrogen gas production rate for the repeated batch process when compared to that of the ordinary batch process this result justified the use of the repeated batch system as a process that enhances biohydrogen production.